Utilization of Local Healing Practices Among Patients Admitted to a Remote Tertiary Care Hospital in Eastern Bhutan: A Cross‐Sectional Study - Pelden Wangchuk; Phuntsho Norbu; Yeshey Dorjey; Sonam Lhundrup; Thinley Dorji (Health Science Reports, 2026)
ABSTRACT Background and Aims In Bhutan, patients frequently choose between allopathic health professionals and Traditional Medicine ( Sowa Rigpa ) practitioners based on personal faith and cultural preferences. However, beyond these formally recognized systems, uncertified local healers provide alternative cultural and spiritual healing methods that are often associated with ethical dilemmas and delayed clinical management. This study aimed to comprehensively describe the socio‐demographic characteristics, clinical diagnoses, and specific types of local healing treatments received by patients admitted to a remote tertiary care hospital in eastern Bhutan. Methods A cross‐sectional study was conducted at the Eastern Regional Referral Hospital in Mongar from January 1 to December 31, 2021. The study included all hospitalized patients who had consulted a local healer prior to hospital admission, identified through structured admission interviews. Data were gathered via interviewer‐administered standardized pro forma to ensure accuracy across all demographics, particularly given educational disparities, and analyzed using SPSS software (version 23). Ethical clearance was obtained from the Research Ethical Board of Health, Ministry of Health, Bhutan. Results Among 5,041 total admissions during the study period, 8.6% ( n = 434) had utilized local healers prior to presentation. These individuals were predominantly young adults (38.7%), married females (63.4%), farmers (56.5%), and individuals with no formal education (58.8%). Motivations for seeking traditional care included positive past experiences, family pressure, community hearsay, firm belief in traditional healing, and skepticism toward allopathic medicine. Furthermore, 80% reported healthcare delays based on healer advice, with primary presentations spanning trauma or surgical conditions (27%), pregnancy and delivery (22.8%), and non‐communicable diseases (18.4%). Nearly all patients (98.4%) received treatments lasting under 7 days, and over half spent less than Nu 1,000. A pediatric subgroup analysis of 60 children (0–12 years) who received Local Healing revealed that most treatment episodes were brief (median 1 day, IQR 1–2) and moderately costly (median Nu 1,000, IQR 300–4,250), with trauma as the leading diagnosis among school‐age children and non‐specific (‘Other’) conditions predominating in younger children. Notably, sucking of the genitalia was reported in all pediatric respondents with valid data (100%), raising child‐safeguarding concerns. Conclusion Approximately one in twelve admitted patients initially sought care from local healers, delaying formal medical intervention until traditional methods failed. While shaped by community trust and familial influence, this reliance underscores the need to address pre‐hospital delays through targeted public health messaging.